Professional Social Work in Australia - Lawrence, R.J (ANU Press, 2016)
This is an unchanged republication of the first historical account of the social work profession in Australia. It traces the development of social work education and professional social work in the larger, more industrialised societies overseas before the same developments began in Australia in the late 1920s, and it notes the part played by overseas influence in the subsequent 30-odd years. The book concentrates on the development of training bodies and their courses, the spread of qualified social workers into various fields of employment in Australia's expanding health and welfare services, and the growth of professional associations and their programmes. The author assesses the occupational group in terms of accepted attitudes towards the established professions. He concludes with a discussion of major contemporary issues facing the Australian social work profession.